Identifying and ranking employer brand improvement strategies in post-COVID 19 tourism and hospitality. (July 2023) - Bagheri, Moslem; Baum, Tom; Mobasheri, Ali Asghar; Nikbakht, Amin
This study aims to identified and ranked employer brand strategies in post-COVID-19 tourism and hospitality, considering the significance of employer branding as one of the most important elements for attracting and retaining key employees.In this study, we initially develop a model by systematically reviewing the literature. And in the subsequent quantitative analysis, the strategies identified are tested through a questionnaire survey and ranked by a panel of industry experts and analyzed data using the R-SWARA method.Results show that the most important employer brand strategies in post-COVID-19 tourism and hospitality were "paying increased attention to social responsibility", "developing reliable and sustainable internal/external relationships" and "assessing the effect of brand re-building measures on the social image of the organization". The analysis of the studies conducted dealing with post-COVID-19 employer branding demonstrates that none of these investigations proposed a comprehensive framework of strategies for employer brand promotion. Exploring the literature also revealed that, despite the significance of employer brand in times of economic crisis, this topic has been ignored by researchers although it points to an obvious gap in the literature on employer brand in tourism and hospitality.